Development and application of molecular methods (PCR) for detection of Tasmanian Atlantic salmon reovirus. Issue 8 (16th August 2014) - Zainathan, S C; Carlile, G; Carson, J; McColl, K A; Crane, M St. J; Williams, L M; Hoad, J; Moody, N J G; Aiken, H M; Browning, G F; Nowak, B F
Abstract Molecular (PCR) diagnostic tests for the detection and identification of aquareovirus in general, and Tasmanian Atlantic salmon reovirus (TSRV) specifically, were developed, and their diagnostic sensitivity and specificity were determined and compared with virus isolation in cell culture. Intralaboratory and interlaboratory comparison of PCR (conventional hemi‐nested RT‐PCR & RT‐qPCR) and virus isolation in cell culture using finfish cell lines, CHSE‐214 and EPC, was carried out for the detection and identification of TSRV using field samples of farmed Atlantic salmon Salmo salar, L. from various aquaculture sites around Tasmania. The interlaboratory comparison of diagnostic methods was carried out between two laboratories, AAHL‐CSIRO and DPIPWE‐Tasmania. A total of 144 fish from nine sites (12–33 fish per site) were sampled from two regions of Tasmania (Tamar River estuary in the north and Huon River estuary in the south‐east) during late spring to early summer of 2009, and the data were analysed using different statistical approaches. The prevalence of TSRV ranged from 6% to 22% in both regions. All the diagnostic methods (data from both laboratories) had high specificity, while the estimated sensitivity varied between tests with RT‐qPCR being the most sensitive (95.2%) method followed by virus isolation and then conventional hemi‐nested RT‐PCR.